Notary Responsibilities of Protocol Holders Toward A Copy of Minuta Due Which Has Not Signed Complete - James Pala Joewono; Nynda Fatmawati Octarina (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Responsibilities of the Notary Protocol Holder for Copies of the Minutes of Deed that have not been Signed in Complete. This study aims to determine the actions of the protocol holder Notary Public if there is a request for a copy of the minutes of the deed whose incomplete signature and legal consequences if the Notary holder of the protocol provides a copy of the minutary deed whose incomplete signature . This study uses normative juridical law research and is equipped with several approaches, namely the statutory approach, conceptual approach and historical approach. Public Notary is a public official who is authorized to make an authentic deed and has other authority as referred to in Law Number 2 of 2014 concerning Amendment to Law Number 30 of 2004 concerning Notary Position. When the authority is given then the responsibility will be attached to the notary for the transfer of the protocol, including to the notary recipient of the notary protocol and it is incumbent upon the Notary to provide a copy of the minutes of deed when someone comes to request the copy and in fact there are also found the minutes of the deed not signed completely. Based on this, the problem arises regarding the first, What is the action of the protocol holder Notary Public if there is a request for a copy of the minutes of deed that has not yet completed the signature? second, the legal consequences if the Notary of the protocol holder gives a copy of the minutes of deed whose incomplete signature. The results found in this study are that the Notary Public does not need to issue a request for a copy of the Minutes whose signature is not complete at the request of anyone, and the Public Notary can make a statement that the Minutes of the Deed requested by the parties are incomplete or incomplete signed by the parties.